2016
DOI: 10.1111/jnc.13744
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the neuronal localization and trafficking of CLN3 in juvenile neuronal ceroid lipofuscinosis

Abstract: Juvenile neuronal ceroid lipofuscinosis, the most common neurodegenerative disease affecting children, is caused by mutations of the CLN3 gene encoding CLN3, a transmembrane protein with so far undefined function. The embryonic expression of the gene has not been studied in detail before. Moreover, the protein CLN3 was mostly localized on the subcellular level to lysosomes but the exclusiveness is still under debate. Here, we analyze the expression pattern of murine CLN3 at different developmental stages by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…A significant localisation of the CLN3 orthologue of fission and budding yeasts, Btn1p, has been shown at the Golgi complex [71] and also reported for GFP-tagged CLN3 in mammalian cells [72]. Moreover, untagged CLN3 has been shown to localise at late-endosomes and lysosomes [73]. However, the functional localisation of CLN3 is still matter of debate.…”
Section: Ncl Proteins and Er Stressmentioning
confidence: 82%
“…A significant localisation of the CLN3 orthologue of fission and budding yeasts, Btn1p, has been shown at the Golgi complex [71] and also reported for GFP-tagged CLN3 in mammalian cells [72]. Moreover, untagged CLN3 has been shown to localise at late-endosomes and lysosomes [73]. However, the functional localisation of CLN3 is still matter of debate.…”
Section: Ncl Proteins and Er Stressmentioning
confidence: 82%
“…Disturbed synaptic transmission and impaired short-term plasticity are in line with the proposed dysfunction of CLN3 protein, along with the neurodegenerative processes in patients and in the respective mouse models. CLN3 is localized in synaptosomes ( Luiro et al, 2001 ), in axonal compartments, and in synaptic spines ( Oetjen et al, 2016 ). The proposed role of CLN3 in endocytosis and endosomal functions provides a direct link to short-term plasticity and suggests a role of CLN3 in neuronal transmission.…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to reduce the possibility of mis-folding as far as possible by inserting YFP at the extreme N-terminus of both CLN7 and CLN3 coding sequences. Many groups have used N-terminal fusions of GFP to CLN3 in a variety of models without retention of the protein in the ER (Codlin and Mole, 2009, Huber et al, 2014, Oetjen et al, 2016) and GFP-CLN3 is functional in both yeast (Codlin and Mole, 2009) and Dictyostelium (Huber et al, 2014). In contrast, we and others have shown that truncated forms of CLN3—or adding epitope tags or GFP to the C-terminus—does lead to ER retention and a very different sub-cellular staining pattern than that we see here (example studies include Haskell et al, 1999, Jarvela et al, 1999, Tuxworth et al, 2009).…”
Section: Discussionmentioning
confidence: 99%